DC resistivity investigation in a fractured aquifer system contaminated by leachate from an old dump - Moreira, César Augusto [UNESP]; Leandro, Carolina Gonçalves; Lopes, Camila Trindade; Ilha, Lenon Melo (My University, 2017)
The dumps are areas of final disposal of solid wastes directly into the soil, with no technical criteria or collecting systems of gases or liquids. A large part of Brazilian municipalities have used this extreme damaging alternative to the environment up to the year 2010, when a federal law made compulsory the installation of sanitary landfills. However, large parts of the dumps were simply abandoned, although some eventually go through treatment after assessments of the state environmental agencies. This work presents the results of a geophysical investigation in a dump deactivated in 2004 in a small city in southern Brazil, where previous investigations have revealed contamination of soil and groundwater by leachate. Structural analyzes in the area of study combined to geological data from monitoring wells indicate the presence of contaminants in fractured granite, with a wide variation in the thickness of soil, saprolite and groundwater level. The integration of chemical analyses of the groundwater with electrical resistivity tomography (ERT) in 2D and 3D processing, revealed the existence of large contaminated areas within the limits of the dump flowing into the aquifer partially free up to 5m depth. Such areas may decrease gradually with the increase in depth and between 9m and 19m contaminated zones clearly predominate, associated with the flow in the fractured aquifer. The indication of restricted and oriented zones suggests the targeting and accumulation of contaminants in two systems of preferential fractures. The discovery of these zones is fundamental for planning and the installation of pumping and decontamination systems of groundwater, considering a declining production of leachate since the closure of the dump.
Keywords: Contamination; Electric resistivity tomography; Fractured aquifer; Leachate; Organic matter